Toner and method for producing the same

JP7638745B2Active Publication Date: 2025-03-04CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021045565
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-03-04
Estimated Expiration
2041-03-19

AI Technical Summary

Benefits of technology

【0010】 本開示により、優れた低温定着性を示した上で、優れたエンボス転写性を示すトナーを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638745000011
    Figure 0007638745000011
  • Figure 0007638745000001
    Figure 0007638745000001
  • Figure 0007638745000002
    Figure 0007638745000002
Patent Text Reader

Abstract

To provide a toner that exhibits excellent low temperature fixability and additionally exhibits excellent emboss transferability.SOLUTION: A toner has a toner particle containing a binder resin. The binder resin contains a first resin and a second resin. The first resin is a crystalline resin. The second resin is an amorphous resin. On a cross section of the toner particle observed by a transmission electron microscope, a matrix-domain structure is present which consists of a matrix including the first resin and domains including the second resin. In the total area combining the matrix and the domains, the ratio of the area occupied by the matrix including the first resin is 35 area% or more and 70 area% or less. Hydrocarbon group index (Ge) / hydrocarbon group index (DIA) after the toner is washed with hexane is 1.10 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used in electrophotographic systems, electrostatic recording systems, electrostatic printing systems, toner jet systems, and the like, and a method for producing the toner. [Background technology]

[0002] In recent years, as full-color electrophotographic copying machines have come into widespread use, in addition to higher speed and higher image quality, there is also a demand for additional performance improvements such as energy saving performance, shorter recovery time from sleep mode, compatibility with a wide variety of media, etc. Specifically, as a toner that responds to energy saving, there is a demand for a toner that can be fixed at a lower temperature and has excellent low-temperature fixing properties in order to reduce power consumption in the fixing process.

[0003] The toner described in Patent Document 1 uses a crystalline vinyl resin with sharp melting properties as the main binder, which enables excellent low-temperature fixability. The toners described in Patent Documents 2 and 3 have a matrix domain structure, and the crystalline resin with sharp melting properties forms the matrix, which enables excellent low-temperature fixability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-130243 A [Patent Document 2] JP 2014-059489 A [Patent Document 3] JP 2014-142632 A Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, embossed paper, one of the many types of media, has an uneven surface, which means that toner transferability to the concave parts during the transfer process is poor, and image density differences tend to occur between the concave and convex parts. Therefore, there is a demand for a toner with excellent emboss transferability that does not cause image density differences even on embossed paper.

[0006] The toner described in Patent Document 1 uses a crystalline resin with high molecular mobility, which causes charge diffusion and leakage to members such as the drum and intermediate transfer belt (ITB), lowering the charge on each toner particle. As a result, the electric field driving force becomes smaller, and it has been found that the emboss transferability may be deteriorated.

[0007] The toner described in Patent Document 2 has a toner particle surface composed of different materials, crystalline resin and amorphous resin, so that electric charges are trapped at the interface, the diffusion of electric charges is insufficient, and the amount of charge on the contact surface is high. As a result, the electrostatic adhesion to the member is high, and the emboss transferability may be poor. In addition, the toner described in Patent Document 3 has a toner particle surface covered with a shell of amorphous resin with low molecular mobility, so that the diffusion of electric charges is insufficient, and the amount of charge on the contact surface is high. As a result, the electrostatic adhesion to the member is high, and the emboss transferability may be poor.

[0008] The present disclosure provides a toner that exhibits excellent low-temperature fixing property and also exhibits excellent emboss transferability. [Means for solving the problem]

[0009] The present disclosure relates to a toner having toner particles containing a binder resin, The binder resin contains a first resin and a second resin, the first resin is a crystalline resin; the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, The first resin More than 90% of the area of ​​the The matrix, The first resin calculated based on the spectrum intensity measured by TEM-EDX. The second resin The ratio of the second resin in the ratio is 80 mass% or more.There is a matrix domain structure consisting of domains, an area ratio of the matrix including the first resin to a total area of ​​the matrix and the domain is 35 area % or more and 70 area % or less; The toner has a hydrocarbon group index (Ge) / hydrocarbon group index (DIA) of 1.10 or more after the toner is washed with hexane. [The hydrocarbon group index (Ge) is the index of the hydrocarbon group at 2800 cm corresponding to the stretching vibration of CH in the FT-IR spectrum obtained by the ATR method using Ge as the ATR crystal and at an infrared light incidence angle of 45°. -1 ~2900cm -1 The maximum absorption peak intensity in the range A(Ge) corresponds to the stretching vibration of C=O at 1500 cm -1 ~1800cm -1 The DIA is the value of A(Ge) / B(Ge) when the maximum absorption peak intensity in the range is B(Ge). The DIA is the value of the maximum absorption peak intensity at 2800 cm corresponding to the stretching vibration of CH in the FT-IR spectrum obtained by the ATR method using diamond as the ATR crystal and an infrared light incidence angle of 45°. -1 ~2900cm -1 The maximum absorption peak intensity in the range of A(DIA) is 1500 cm corresponding to the stretching vibration of C=O. -1 ~1800cm -1 The value of A(DIA) / B(DIA) is calculated when B(DIA) is the maximum absorption peak intensity in the range. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a toner that exhibits excellent low-temperature fixing property and also excellent emboss transferability. [Brief description of the drawings]

[0011] [Figure 1] Example of a thermal sphering treatment device DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. (Meth)acrylic acid ester means acrylic acid ester and / or methacrylic acid ester. "Monomer unit" refers to one section of carbon-carbon bond in the main chain of a polymer in which vinyl-based monomers are polymerized, and one unit is defined as one unit. The vinyl-based monomer can be represented by the following formula (Z). [ka]

[0013] In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.

[0014] The present disclosure relates to a toner having toner particles containing a binder resin, The binder resin contains a first resin and a second resin, the first resin is a crystalline resin; the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, a matrix domain structure is present that is composed of a matrix containing the first resin and a domain containing the second resin, an area ratio of the matrix including the first resin to a total area of ​​the matrix and the domain is 35 area % or more and 70 area % or less; The toner has a hydrocarbon group index (Ge) / hydrocarbon group index (DIA) of 1.10 or more after the toner is washed with hexane. [The hydrocarbon group index (Ge) is the index of the hydrocarbon group at 2800 cm corresponding to the stretching vibration of CH in the FT-IR spectrum obtained by the ATR method using Ge as the ATR crystal and at an infrared light incidence angle of 45°.-1 ~2900cm -1 The maximum absorption peak intensity in the range is A(Ge), and the 1500 cm -1 ~1800cm -1 The DIA is the value of A(Ge) / B(Ge) when the maximum absorption peak intensity in the range is B(Ge). The DIA is the value of the maximum absorption peak intensity at 2800 cm corresponding to the stretching vibration of CH in the FT-IR spectrum obtained by the ATR method using diamond as the ATR crystal and an infrared light incidence angle of 45°. -1 ~2900cm -1 The maximum absorption peak intensity in the range of A(DIA) is 1500 cm corresponding to the stretching vibration of C=O. -1 ~1800cm -1 The value of A(DIA) / B(DIA) is calculated when B(DIA) is the maximum absorption peak intensity in the range.

[0015] According to the above toner, it is possible to provide a toner that achieves both low-temperature fixing property and emboss transferability. As a result of intensive research, the present inventors have found that the above-mentioned problem can be solved by controlling the matrix domain structure of the crystalline resin and the amorphous resin, the area occupied by the matrix containing the crystalline resin, and the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) after washing the toner with hexane within specific ranges.

[0016] The inventors speculate that the reason for solving the above problem is as follows. The transferability of the toner is determined by the magnitude relationship between the electric field driving force due to the electric field and the adhesive force with members such as a drum or ITB, and the toner can be transferred when the electric field driving force exceeds the adhesive force. The reason why the emboss transferability is reduced is that when the gap with a member such as the recess of the embossed paper is large, the electric field driving force is reduced accordingly, and the transferability of the toner is deteriorated. In addition, the electric field driving force is largely dependent on the charge amount of one toner particle, whereas the adhesive force is largely dependent on the charge amount of the contact surface with the member. Therefore, if the charge amount of the toner is blindly increased in order to increase the electric field driving force, the adhesive force also increases at the same time, and this does not lead to improvement of the emboss transferability. Furthermore, it is possible to add a large amount of inorganic fine particles to the toner surface in order to reduce the non-electrostatic adhesive force, but the inorganic fine particles hinder fixing, resulting in poor low-temperature fixability.

[0017] The present inventors have discovered that by controlling the states of existence of the crystalline resin and the amorphous resin in a matrix domain structure composed of a matrix containing a crystalline resin and a domain containing an amorphous resin, it is possible to obtain excellent low-temperature fixing properties, lower the adhesion force while maintaining the electric field driving force, and obtain excellent emboss transferability. As a result of detailed investigation, it was found that the area occupied by the matrix in the cross section of the toner particle and the states of existence of the crystalline resin and the amorphous resin on the surface and inside of the toner particle have an effect.

[0018] It has a matrix-domain structure consisting of a matrix containing a crystalline resin and a domain containing an amorphous resin, and the area ratio of the matrix containing the first resin to the total area of ​​the matrix and domain combined must be 35 area % or more and 70 area % or less. In addition, it is necessary that the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) after washing the toner with hexane is 1.10 or more.

[0019] By satisfying these requirements, the crystalline resin with high molecular mobility is selectively present in large amounts on the toner particle surface, which promotes charge diffusion on the toner particle surface, suppresses the charge amount on the contact surface, and reduces the electrostatic adhesion. On the other hand, the charge amount per toner particle can be maintained because the charge is trapped at the interface between the crystalline resin and the amorphous resin present inside the toner particle. As a result, by making the matrix of the matrix domain structure a crystalline resin and selectively having a large amount of the matrix present on the toner particle surface, a toner with excellent low-temperature fixing ability, reduced electrostatic adhesion while maintaining the electric field driving force, and excellent emboss transferability was obtained.

[0020] Of the total area of ​​the matrix and domain combined, the area ratio of the matrix is ​​preferably 40 area% or more and 60 area% or less. When the area ratio of the matrix satisfies the above range, the balance between the diffusion of charge by the crystalline resin and the trapping of charge by the interface between the crystalline resin and the amorphous resin is good, improving the emboss transferability. The above area ratio can be controlled by the ratio of the crystalline resin forming the matrix to the amorphous resin forming the domain.

[0021] In the ATR (Attenuated Total Reflection) method, a sample is placed in close contact with a crystal (ATR crystal) that has a higher refractive index than the sample, and infrared light is incident on the crystal at an angle of incidence greater than the critical angle. The incident light then undergoes repeated total reflections at the interface between the sample and the crystal. At this time, the infrared light does not reflect at the interface between the sample and the crystal, but rather penetrates slightly into the sample before being totally reflected. The depth of this penetration depends on the wavelength, the angle of incidence, and the refractive index of the ATR crystal. d p =λ / (2πn1)×[sin 2 θ-(n1 / n2) 2 ] -1 / 2 d p : Penetration depth n1: refractive index of the sample (set to 1.5 in this disclosure) n2: Refractive index of the ATR crystal (refractive index when the ATR crystal is Ge: 4.0, refractive index when the ATR crystal is diamond: 2.4) θ: Incident angle

[0022] Therefore, by changing the refractive index and incident angle of the ATR crystal, FT-IR spectra with different penetration depths can be obtained. Using this characteristic, the degree of uneven distribution of the matrix containing the crystalline resin on the surface of the toner particles is indexed. As the ATR crystals, a Ge ATR crystal (refractive index: 4.0) and a diamond ATR crystal (refractive index: 2.4) are used. When Ge is used as the ATR crystal, the penetration depth is approximately 200 nm from the sample surface, and when diamond is used, the penetration depth is approximately 700 nm from the sample surface.

[0023] The hydrocarbon group index (Ge) is the value obtained by measuring the FT-IR spectrum at an ATR method with Ge as the ATR crystal and an infrared light incidence angle of 45° at 2800 cm corresponding to the stretching vibration of CH. -1 ~2900cm -1 The maximum absorption peak intensity in the range is A(Ge), and the 1500 cm -1 ~1800cm -1 This is the value of A(Ge) / B(Ge) when the maximum absorption peak intensity in the range is B(Ge).

[0024] The hydrocarbon group index (DIA) was determined by the ATR method using diamond as the ATR crystal at an infrared light incidence angle of 45°. The FT-IR spectrum was obtained by measuring the 2800 cm -1 ~2900cm -1 The maximum absorption peak intensity in the range of A(DIA) is 1500 cm corresponding to the stretching vibration of C=O. -1 ~1800cm -1 is the value of A(DIA) / B(DIA) when the maximum absorption peak intensity in the range is B(DIA).

[0025] 2800 cm corresponds to the CH stretching vibration -1 ~2900cm -1The maximum absorption peak intensity in the range of 150 indicates the presence of alkyl groups. 0cm -1 ~1800cm -1 The maximum absorption peak intensity in the range of represents the presence of a carbonyl group. Therefore, the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) represents the ratio of the amount of crystalline resin at a depth of about 200 nm to the amount of crystalline resin at a depth of about 700 nm from the toner particle surface, that is, represents the degree of uneven distribution of the matrix containing the crystalline resin on the toner particle surface.

[0026] After the toner is washed with hexane, the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) is preferably 1.20 or more. When the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) is 1.20 or more, the amount of crystalline resin present on the toner particle surface increases, which promotes charge diffusion and improves emboss transferability. There is no particular upper limit to the hydrocarbon group index (Ge) / hydrocarbon group index (DIA), but it is preferably 1.60 or less, and more preferably 1.40 or less.

[0027] Methods for controlling the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) include the presence or absence of surface treatment of toner particles by heating, the hot air treatment temperature, the presence or absence of a core-shell structure, and the type and amount of shell agent added. Increasing the hot air treatment temperature causes more low-viscosity crystalline resin to precipitate on the surface, and the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) increases. In addition, using an appropriate amount of crystalline material as a shell agent increases the hydrocarbon group index (Ge) / hydrocarbon group index (DIA).

[0028] In cross-sectional observation of a toner particle, the number-average equivalent circle diameter of the domains is preferably 20 nm to 500 nm, more preferably 100 nm to 300 nm. When the number-average equivalent circle diameter of the domains satisfies the above range, the dispersibility of the domains in the toner is improved, charge trapping at the interface between the crystalline resin and the amorphous resin is promoted, and emboss transferability is improved.

[0029] Methods for controlling the number-average equivalent circle diameter of the domains include the relationship between the SP values ​​of the matrix and domain resins, the kneading temperature and screw rotation speed in the melt kneading process, and the stirring rotation speed in the aggregation process. If the SP values ​​of the matrix and domain resins are close, the compatibility between the matrix and domains increases, and the number-average equivalent circle diameter of the domains decreases. In addition, increasing the screw rotation speed or stirring rotation speed increases the shear force on the resin, and the number-average equivalent circle diameter of the domains decreases.

[0030] The charge decay rate coefficient of the toner particles measured in a 30°C, 80% RH environment is preferably 10 to 70, more preferably 20 to 50. When the charge decay rate coefficient satisfies the above range, charge diffusion is improved, and emboss transferability is improved. Methods for controlling the charge decay rate coefficient measured in a 30°C, 80% RH environment include the SP value and molecular structure of the resin, and the material composition of the toner particle surface. If a large amount of resin with low molecular mobility is present on the toner particle surface, the charge decay rate coefficient becomes small.

[0031] The binder resin contains a first resin, and the first resin is a crystalline resin. As the crystalline resin, a known crystalline resin can be used. For example, a crystalline vinyl resin, a crystalline polyester resin, a crystalline polyurethane resin, and a crystalline polyurea resin can be mentioned. In addition, ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-acrylic acid copolymer can also be mentioned.

[0032] From the viewpoint of low-temperature fixability, crystalline vinyl resins and crystalline polyester resins are preferred. Also, a hybrid resin in which a vinyl resin and a polyester resin are combined may be used. The resin preferably contains a vinyl resin, more preferably is a vinyl resin, and preferably has a first monomer unit represented by the following formula (1). The first resin is preferably a vinyl resin having a monomer unit represented by the following formula (1). The vinyl resin is a polymer or copolymer of a compound containing a group having an ethylenically unsaturated bond such as a vinyl group. Examples of the group having an ethylenically unsaturated bond include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group. [ka]

[0033] In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms. The first monomer unit represented by the above formula (1) has R 1 The first monomer unit represented by formula (1) is preferably a monomer unit derived from a first polymerizable monomer which is at least one selected from the group consisting of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms, and the presence of this moiety makes it easy to exhibit crystallinity. The first resin has the first monomer unit represented by formula (1) above, and thus has a comb-shaped crystal structure, which appropriately suppresses molecular mobility, improves charge diffusion, and improves emboss transferability.

[0034] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0035] Among these, from the viewpoint of low temperature fixability, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 36 carbon atoms is preferable, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 30 carbon atoms is more preferable, and at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate is even more preferable. The monomers forming the first monomer unit may be used alone or in combination of two or more kinds.

[0036] The content of the first monomer unit in the first resin is preferably 30.0% by mass or more and 80.0% by mass or less, more preferably 40.0% by mass or more and 70.0% by mass or less. When the content of the first monomer unit in the first resin satisfies the above range, the charge diffusion becomes good, and the emboss transferability becomes better. When the crystalline resin has monomer units derived from two or more kinds of (meth)acrylic acid esters having alkyl groups having 18 to 36 carbon atoms, the content of the first monomer unit is determined based on the total quality of those monomer units. Represents the quantity ratio.

[0037] SP value of the first monomer unit (J / cm 3 ) 0.5is SP1, SP1 is preferably less than 20.00, more preferably 19.00 or less, and even more preferably 18.40 or less. The lower limit is not particularly limited, but is preferably 17.00 or more.

[0038] Here, the SP value is an abbreviation for solubility parameter, and is a value that serves as an index of solubility. The calculation method will be described later. The unit of the SP value is (J / cm 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / cm 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of

[0039] The first resin preferably has a second monomer unit different from the first monomer unit, which is at least one selected from the group consisting of monomer units represented by the following formula (2) and the following formula (3). The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 When it is, it is preferable to satisfy the following relational formula (4): It is more preferable to satisfy the following relational formula (4'): There is no particular upper limit for SP2, but it is preferably 30.00 or less. 21.00 (J / cm 3 ) 0.5 ≦SP2 (4) 25.00 (J / cm 3 ) 0.5 ≦SP2 (4´)

[0040] When the SP2 of the second monomer unit satisfies the above formula (4), the second monomer unit has high polarity, and a polarity difference occurs between the first and second monomer units. This polarity difference promotes crystallization of the first monomer unit, thereby obtaining excellent low-temperature fixability. Specifically, the first monomer unit is incorporated into a crystalline resin, and the first monomer units aggregate with each other to exhibit crystallinity.

[0041] In general, the crystallization of the first monomer unit is inhibited when other monomer units are incorporated, so that the crystalline resin is less likely to exhibit crystallinity. This tendency becomes more pronounced when multiple types of monomer units are randomly bonded together in one molecule of the crystalline resin. However, by using a first polymerizable monomer having a polarity difference and a second polymerizable monomer forming the second monomer unit, it is believed that the first polymerizable monomer and the second polymerizable monomer can be bonded to a certain degree of continuity during polymerization, rather than being randomly bonded. As a result, a block is formed in which the first monomer units are assembled together, and the crystalline resin becomes a block copolymer, which makes it possible to increase the crystallinity even when other monomer units are incorporated, and excellent low-temperature fixability is obtained.

[0042] [ka]

[0043] (In formula (2), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 3 teeth, Nitrile groups (-C≡N), Amide group (-C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy groups, -COOR 31 (R 31 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), Urea group (-NH-C(=O)-N(R 33 )2(Two R 33 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH2)2NHCOOR 34 (R 34 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH2)2-NH-C(=O)-N(R 35 )2(Two R 35 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 4 represents a hydrogen atom or a methyl group. [ka]

[0044] (In formula (3), R 5 represents an alkyl group having 1 to 4 carbon atoms, R 6 represents a hydrogen atom or a methyl group. Specific examples of the second polymerizable monomer that forms the second monomer unit include the following polymerizable monomers. Preferably, a polymerizable monomer that can form the monomer unit represented by the above formula (2) or (3) is used. Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.

[0045] Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method.

[0046] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.

[0047] Among them, monomers having a nitrile group, an amide group, a hydroxyl group, or a urea group are used. More preferably, it is a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a hydroxyl group, and a urea group, and an ethylenically unsaturated bond. Acrylonitrile and methacrylonitrile are particularly preferred.

[0048] Also preferably used as the second monomer unit are vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate. Among these, vinyl esters are preferred from the viewpoint of low-temperature fixability because they are non-conjugated monomers and therefore tend to maintain a suitable reactivity with the first polymerizable monomer and tend to increase the crystallinity of the polymer.

[0049] The content of the second monomer unit in the first resin is preferably 5.0% by mass to 40.0% by mass, and more preferably 10.0% by mass to 30.0% by mass.

[0050] The composition may contain a third monomer unit obtained by polymerizing a third polymerizable monomer not included in the range of the above formula (4) (i.e., different from the first polymerizable monomer and the second polymerizable monomer) within a range that does not impair the mass ratio of the above-mentioned first monomer unit and the second monomer unit. As the third polymerizable monomer, a monomer that does not satisfy the above formula (4) can be used among the monomers exemplified as the above-mentioned second polymerizable monomer.

[0051] For example, the following monomers can also be used: styrene and its derivatives such as styrene and o-methylstyrene, and (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, the third polymerizable monomer is preferably styrene from the viewpoint of charge diffusion. The content of the third monomer unit in the first resin is preferably 5.0% by mass to 50.0% by mass, and more preferably 10.0% by mass to 30.0% by mass.

[0052] SP value of the first monomer unit (J / cm 3 ) 0.5 Assuming that the SP3 is 19.00 or more and 25.00 or less, the SP3 is preferably 19.00 or more and 25.00 or less, and more preferably 19.50 or more and 21.00 or less.

[0053] The binder resin contains a second resin, and the second resin is an amorphous resin. From the viewpoint of trapping electric charges, the second resin is preferably a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof, and more preferably a styrene-acrylic resin. As the styrene-acrylic resin, a styrene-acrylic resin that is normally used in toners can be suitably used.

[0054] Examples of styrene monomers include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. These styrene monomers can be used alone or in combination.

[0055] Examples of (meth)acrylic monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, and n-hexyl (meth)acrylate. Examples of the (meth)acrylate include 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dimethyl phosphate ethyl (meth)acrylate, diethyl phosphate ethyl (meth)acrylate, dibutyl phosphate ethyl (meth)acrylate, and 2-benzoyloxyethyl (meth)acrylate, (meth)acrylonitrile, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, and maleic acid. These (meth)acrylic monomers can be used alone or in combination.

[0056] As the polyester resin, a polyester resin that is usually used in a toner can be suitably used. As a monomer used in the polyester resin, a polyhydric alcohol (a divalent or trivalent or higher alcohol), a polyvalent carboxylic acid (a divalent or trivalent or higher carboxylic acid), an acid anhydride thereof, or a lower alkyl ester thereof can be mentioned.

[0057] Examples of polyhydric alcohols include the following: Examples of dihydric alcohols include the following bisphenol derivatives: polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, etc.

[0058] Other polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. These polyhydric alcohols can be used alone or in combination.

[0059] Examples of polyvalent carboxylic acids include the following. Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.

[0060] Examples of trivalent or higher carboxylic acids, their acid anhydrides, or their lower alkyl esters include the following: 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their acid anhydrides, or their lower alkyl esters. Kill Ester.

[0061] Among these, 1,2,4-benzenetricarboxylic acid (trimellitic acid) or its derivatives such as anhydride are preferably used because they are inexpensive and the reaction can be easily controlled. These polyvalent carboxylic acids can be used alone or in combination.

[0062] <Other resins> The binder resin may contain a third resin other than the first resin and the second resin to such an extent that the effect of the present disclosure is not impaired, for the purpose of improving pigment dispersibility, etc. Examples of such resins include the following: polyvinyl chloride, phenolic resin, natural resin-modified phenolic resin, natural resin-modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, and petroleum-based resin.

[0063] <Wax> The toner particles may contain a wax as necessary. Examples of the wax include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes mainly composed of fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.

[0064] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene saturated fatty acid bisamides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats.

[0065] The wax preferably contains a hydrocarbon wax. The content of the wax is preferably 2.0 parts by mass to 30.0 parts by mass with respect to 100 parts by mass of the binder resin.

[0066] <Coloring agent> The toner particles may contain a colorant as necessary. Examples of the colorant include the following: Black colorants include carbon black, and black toned colorants using a yellow colorant, a magenta colorant, and a cyan colorant. Colorants include pigments. Although they may be used alone, it is more preferable to use a dye and a pigment in combination to improve the clarity of the image in full color images.

[0067] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.

[0068] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0069] Pigments for cyan toner include: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. An example of a dye for cyan toner is CI Solvent Blue 70.

[0070] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.

[0071] These colorants can be used alone or in mixture, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner. The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.

[0072] <Charge control agent> The toner particles may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized, and the amount of triboelectric charge can be optimally controlled according to the development system. As the charge control agent, a known one can be used, but in particular, a metal compound of an aromatic carboxylic acid is preferred, which is colorless, has a high charging speed of the toner, and can stably maintain a constant amount of charge.

[0073] Examples of the negative charge control agent include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonic acid ester on the side chain, polymeric compounds having carboxylate or carboxylate on the side chain, boron compounds, urea compounds, silicon compounds, Calixarenes are examples.

[0074] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, and more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.

[0075] <Inorganic fine particles> The toner may contain inorganic fine particles as required. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner as an external additive. Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and composite oxide fine particles thereof. Among the inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0076] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of ​​50 m 2 / g~400m 2 From the viewpoint of improving durability and stability, it is preferable that the inorganic fine particles as the external additive have a specific surface area of ​​10 m 2 / g~50m 2 In order to achieve both improved fluidity and durability and stability, inorganic fine particles having a specific surface area within the above range may be used in combination.

[0077] The content of the external additive is preferably 0.1 parts by mass to 10.0 parts by mass with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.

[0078] <Developer> The toner can be used as a one-component developer, but it is more preferable to mix the toner with a magnetic carrier and use it as a two-component developer, in that stable images can be obtained over a long period of time.

[0079] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.

[0080] When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio, in terms of the toner concentration in the two-component developer, is preferably 2.0% by mass or more and 15.0% by mass or less, and more preferably 4.0% by mass or more and 13.0% by mass or less.

[0081] <Toner manufacturing method> The method for producing the toner is not particularly limited, and any known method can be used, such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, a dispersion polymerization method, etc. The procedure for producing the toner by the pulverization method will be described below.

[0082] <Raw material mixing process> In the raw material mixing process, materials constituting the toner particles, such as binder resin, and other components such as wax, colorant, and charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (made by Japan (manufactured by Coke Industries Co., Ltd.)

[0083] <Melting and kneading process> Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process. It is possible to control the dispersion state of the first resin and the second resin, the number-average diameter of the domains, and the like, by the kneading temperature in the melt-kneading process, the number of rotations of the screw, and the like.

[0084] <Crushing process> The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0085] <Classification process> Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0086] <Thermal sphering process> In addition, if necessary, after pulverization, the toner particles may be subjected to surface treatment such as spheronization using a Hybridization System (manufactured by Nara Machinery Works), a Mechanofusion System (manufactured by Hosokawa Micron Corporation), a Faculty (manufactured by Hosokawa Micron Corporation), or a Meteor Rainbow MR Type (manufactured by Nippon Pneumatic Co., Ltd.).

[0087] In particular, the surface treatment of toner particles by heating is preferred from the viewpoint of easily controlling the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) since a crystalline resin with low viscosity is precipitated on the surface. In addition, the surface treatment of toner particles by heating as described above is performed in a hydrophobic field, so that highly hydrophobic materials are oriented on the surface, which is also preferred from the viewpoint of controlling the diffusion of electric charges. For example, the surface treatment can be performed by hot air using a thermal sphering treatment device shown in FIG. 1. That is, the toner particles are preferably pulverized toner particles, and more preferably pulverized toner particles that have been heat-treated. The toner manufacturing method preferably includes a step of performing surface treatment of toner particles by hot air to obtain heat-treated toner particles.

[0088] In Fig. 1, the mixture supplied by the material supply means 1 is introduced into an introduction pipe 3 installed on the central axis of a treatment chamber 6 by compressed gas adjusted by a compressed gas adjustment means 2. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 4 installed in the center of the material supply means, and is introduced into eight supply pipes 5 that radiate out in eight directions, and is introduced into the treatment chamber 6 where heat treatment is carried out from a powder particle supply port 14.

[0089] At this time, the flow of the mixture supplied to the processing chamber 6 is regulated by a regulating means 9 for regulating the flow of the mixture provided in the processing chamber 6. The mixture is heat-treated while swirling in the treatment chamber 6, and then cooled.

[0090] Hot air for heat-treating the supplied mixture is supplied from hot air supply means 7, and is introduced into treatment chamber 6 by spirally swirling it using swirling member 13 for swirling the hot air. In terms of configuration, swirling member 13 for swirling the hot air has multiple blades, and the swirling of the hot air can be controlled by the number and angle of the blades. At this time, the approximately conical distribution member 12 can reduce bias in the swirling hot air.

[0091] The hot air supplied into the processing chamber 6 preferably has a temperature at the hot air outlet 11 of the hot air supplying means 7 of 100° C. to 300° C., and more preferably 105° C. to 200° C. If the temperature at the hot air outlet 11 of the hot air supplying means 7 is within the above range, it is possible to uniformly sphericalize the toner particles while preventing fusion or coalescence of the toner particles due to excessive heating of the mixture, and this is preferable because it results in better emboss transferability.

[0092] Furthermore, the heat-treated toner particles are cooled by cold air supplied from cold air supplying means 8 (8-1, 8-2, 8-3). The temperature of the cold air supplied from the cold air supplying means 8 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be prevented without impeding the uniform spheroidization of the mixture. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that:

[0093] Next, the cooled heat-treated toner particles are collected by the collection means 10 at the bottom end of the processing chamber 6. A blower (not shown) is provided ahead of the collection means 10, so that the toner particles are sucked and transported by the blower.

[0094] The powder particle supply port 14 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 10 is provided on the outer periphery of the processing chamber 6 so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 8 is configured to be supplied from the outer periphery of the device to the inner periphery of the processing chamber 6 in a horizontal and tangential direction. The swirling directions of the toner particles supplied from the powder particle supply port 14, the swirling direction of the cold air supplied from the cold air supply means 8, and the swirling direction of the hot air supplied from the hot air supply means 7 are all the same. Therefore, no turbulence occurs in the processing chamber 6, the swirling flow in the device is strengthened, a strong centrifugal force is applied to the toner particles, and the dispersibility of the toner particles is further improved, so that toner particles with a uniform shape and few coalesced particles can be obtained.

[0095] <External addition process> The obtained toner particles may be used as a toner as it is. If necessary, an external additive may be added to the surface of the toner particles to form a toner. As a method for adding an external additive, a method may be mentioned in which the classified toner and various known external additives are mixed in a predetermined amount, and stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.

[0096] Also, the case of producing toner particles by the emulsion aggregation method will be described. In the emulsion aggregation method, toner particles are produced through a dispersion process in which a fine particle dispersion liquid made of the constituent materials of the toner particles is prepared, an aggregation process in which fine particles made of the constituent materials of the toner particles are aggregated and the particle size is controlled until the particle size reaches the toner particle size, a fusion process in which the resin contained in the obtained aggregated particles is fused, a subsequent cooling process, a metal removal process in which the obtained toner is filtered and excess polyvalent metal ions are removed, a filtration / washing process in which the toner particles are washed with ion-exchanged water, etc., and a process in which the washed toner particles are dehydrated and dried, etc.

[0097] <Step of preparing a resin particle dispersion (dispersion step)> The resin microparticle dispersion liquid can be prepared by a known method, but is not limited to these methods.The known methods include, for example, emulsion polymerization method, self-emulsification method, phase inversion emulsification method in which resin is emulsified by adding aqueous medium to the resin solution dissolved in organic solvent, and forced emulsification method in which resin is forcedly emulsified by high temperature treatment in aqueous medium without using organic solvent.

[0098] Specifically, the binder resins such as the first resin and the second resin are dissolved in an organic solvent capable of dissolving them, and a surfactant or a basic compound is added as necessary. In this case, if the binder resin is a crystalline resin having a melting point, it may be dissolved by heating it to above its melting point. Then, while stirring with a homogenizer or the like, an aqueous medium is slowly added to precipitate the resin fine particles. Then, the solvent is removed by heating or decompression to prepare an aqueous dispersion of the resin fine particles. Any organic solvent can be used to dissolve the resin as long as it can dissolve the resin, but it is preferable to use an organic solvent that forms a homogeneous phase with water, such as toluene, from the viewpoint of suppressing the generation of coarse powder.

[0099] The surfactant used in the emulsification is not particularly limited, but examples thereof include anionic surfactants such as sulfate salts, sulfonate salts, carboxylate salts, phosphate esters, and soap salts; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more.

[0100] Examples of the basic compound used in the dispersion step include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. The basic compound may be used alone or in combination of two or more.

[0101] The 50% particle size (D50) based on volume distribution of the binder resin particles in the aqueous dispersion of the resin particles is preferably 0.05 μm to 1.00 μm, and more preferably 0.05 μm to 0.40 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it becomes easy to obtain toner particles with a weight average particle size of 3 μm to 10 μm, which is appropriate for toner particles. The 50% particle size (D50) based on volume distribution is measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.).

[0102] <Colorant particle dispersion> The colorant particle dispersion liquid used as necessary can be prepared by the following known methods, but is not limited to these methods. It can be prepared by mixing the colorant, the aqueous medium, and the dispersant with a mixer such as a known stirrer, emulsifier, or disperser. The dispersant used here can be a known one such as a surfactant or a polymer dispersant. Both the surfactant and the polymer dispersant can be removed in the washing step described below, but from the viewpoint of washing efficiency, the surfactant is preferred.

[0103] Examples of the surfactant include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, nonionic surfactants or anionic surfactants are preferred. A nonionic surfactant and an anionic surfactant may be used in combination. The surfactant may be used alone. The concentration of the surfactant in the aqueous medium is preferably from 0.5% by mass to 5% by mass.

[0104] The content of the colorant particles in the colorant particle dispersion is not particularly limited, but is preferably 1% by mass to 30% by mass with respect to the total mass of the colorant particle dispersion. From the viewpoint of dispersibility of the colorant in the toner particles finally obtained, the dispersed particle size of the colorant particles in the aqueous dispersion of the colorant is preferably 0.50 μm or less in terms of the 50% particle size (D50) based on volume distribution. For the same reason, it is preferably 2 μm or less in terms of the 90% particle size (D90) based on volume distribution. The dispersed particle size of the colorant particles dispersed in the aqueous medium is measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso).

[0105] Known mixers such as stirrers, emulsifiers, and dispersers used when dispersing a colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint shakers. These may be used alone or in combination.

[0106] <Wax particle dispersion> If necessary, a wax microparticle dispersion may be used. The wax microparticle dispersion can be prepared by the following known methods, but is not limited to these methods. The wax microparticle dispersion can be prepared by adding wax to an aqueous medium containing a surfactant, heating the mixture to above the melting point of the wax, dispersing the mixture into particles using a homogenizer with strong shearing power (e.g., M Technique's "Clearmix W Motion") or a pressure discharge type disperser (e.g., Gaulin Homogenizer) and then cooling the mixture to below the melting point.

[0107] The dispersed particle size of the wax microparticle dispersion in the wax aqueous dispersion is preferably 0.03 μm to 1.0 μm, more preferably 0.10 μm to 0.50 μm, in terms of the 50% particle size (D50) based on volume distribution. It is also preferable that no coarse particles of 1 μm or more exist.

[0108] By setting the dispersed particle size of the wax particle dispersion within the above range, it becomes possible to finely disperse the wax in the toner particles, maximize the exudation effect during fixing, and obtain good separation properties. The dispersed particle size of the wax particle dispersion dispersed in the aqueous medium can be measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150: manufactured by Nikkiso).

[0109] <Mixing process> In the mixing step, a mixed liquid is prepared by mixing the first resin particle dispersion liquid, the second resin particle dispersion liquid, and, if necessary, the wax particle dispersion liquid and the colorant particle dispersion liquid, etc. This can be performed using a known mixing device such as a homogenizer or a mixer.

[0110] <Step of forming aggregate particles (aggregation step)> In the aggregation step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates of the desired particle size. At this time, an aggregating agent is added and mixed as necessary, and at least one of heating and mechanical power is appropriately applied to form aggregates in which the resin fine particles and, as necessary, the wax fine particles and the colorant fine particles are aggregated. By adjusting the mechanical power, it is possible to control the dispersion state of the first resin and the second resin, the number average diameter of the domains, and the like.

[0111] As the flocculant, a flocculant containing a divalent or higher metal ion may be used as necessary. A flocculant containing a divalent or higher metal ion has a high flocculating power, and the purpose can be achieved by adding a small amount. These flocculants can also ionically neutralize the ionic surfactant contained in the resin particle dispersion, the wax particle dispersion, and the colorant particle dispersion. As a result, the resin particle, the wax particle, and the colorant particle are easily aggregated due to the effects of salting out and ionic crosslinking.

[0112] In the aggregation process, new resin particle dispersion may be added after the aggregates are formed, if necessary. A core-shell structure can be realized by adding new resin particle dispersion and aggregating the aggregates. The hydrocarbon group index (Ge) / hydrocarbon group index (DIA) can be controlled by adjusting the material used for the shell and the amount added. When an appropriate amount of crystalline resin is used as a shell agent, the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) becomes large, and when an appropriate amount of amorphous resin is used, the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) becomes small.

[0113] The aggregation step is a step of forming aggregates of the same size as toner particles in an aqueous medium. The weight average particle size of the aggregates produced in the aggregation step is preferably 3 μm to 10 μm. The weight average particle size can be measured using a particle size distribution analyzer (Coulter Multisizer III, manufactured by Coulter) using the Coulter method.

[0114] <Fusion process> In the fusion step, an aggregation terminator may be added to the dispersion containing the aggregates obtained in the aggregation step under stirring in the same manner as in the aggregation step. Examples of the aggregation terminator include a basic compound that shifts the equilibrium of the acidic polar group of the surfactant to the dissociation side and stabilizes the aggregated particles. In addition, examples of the aggregation terminator include a chelating agent that partially dissociates the ionic bridge between the acidic polar group of the surfactant and the metal ion serving as the aggregating agent, and forms a coordinate bond with the metal ion to stabilize the aggregated particles.

[0115] After the dispersion state of the aggregated particles in the dispersion liquid becomes stable due to the action of the aggregation terminator, the aggregated particles are fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the binder resin. By adjusting the temperature during fusion, it is also possible to control the number-average diameter of the domains. The weight-average particle diameter of the obtained toner particles is preferably about 3 μm to 10 μm.

[0116] <Filtration process, washing process, drying process, classification process> Thereafter, a filtration process for filtering out the solid content of the toner particles, a washing process, a drying process, and a classification process for particle size adjustment are performed as necessary to obtain toner particles. The obtained toner particles may be used as a toner as is. The obtained toner particles may be mixed with inorganic fine particles and, if necessary, other external additives to obtain a toner. The toner particles, inorganic fine particles, and other external additives may be mixed using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).

[0117] The methods for measuring various physical properties are described below. <Separation of toner particles from toner> The toner particles can be separated from the toner by the following method. Add 200 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and break up the toner clumps with a spatula or the like. The centrifuge tubes were placed in a shaker (Iwaki Sangyo Co., Ltd. "KM Shaker" (model The solution is shaken for 20 minutes at 350 reciprocations per minute in a 500 rpm (V.S.X) rotor. After shaking, the solution is transferred to a glass tube for a swing rotor (50 mL) and centrifuged at 3,500 rpm for 30 minutes in a centrifuge. After centrifugation, toner particles are present in the top layer in the glass tube, and inorganic fine particles are present in the aqueous solution side in the lower layer. The toner particles in the top layer are collected.

[0118] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Third separation: The soluble fraction (first resin, wax) obtained in the second separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.

[0119] (When a third resin is included) First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin, third resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The soluble fraction (second resin, third resin) obtained in the first separation is dissolved in toluene at 23° C., and the soluble fraction (third resin) is separated from the insoluble fraction (second resin). Third separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Fourth separation: The soluble fraction (first resin, wax) obtained in the third separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.

[0120] (Measurement of the Contents of the First Resin and the Second Resin in the Binder Resin in the Toner) In each of the separation steps, the masses of the soluble and insoluble components are measured to calculate the contents of the first resin and the second resin in the binder resin in the toner.

[0121] <Method of Identifying and Measuring the Content of Each Monomer Unit Constituting the First, Second, and Third Resins> The identification and content ratio of each monomer unit in the resin are measured by 1H-NMR was performed under the following conditions. Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 Measurement temperature: 30℃ Sample: 50 mg of the measurement sample is placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) is added as a solvent, and this is dissolved in a thermostatic bath at 40°C to prepare the sample.

[0122] Obtained 1 From the H-NMR chart, a peak that is independent of the peaks that are assigned to the components of the first monomer unit and the peaks that are independent of the peaks that are assigned to the components of the other monomer units is selected, and the integral value S1 of this peak is calculated. Among the peaks attributable to the constituent elements, a peak independent of the peaks attributable to the constituent elements of other monomer units is selected, and the integral value S2 of this peak is calculated. Furthermore, when the resin has a third monomer unit, a peak that is independent of the peaks attributable to the components of the third monomer unit is selected from the peaks attributable to the components of the other monomer units, and the integral value S3 of this peak is calculated. The content ratio of the first monomer unit is determined using the above integral values ​​S1, S2, and S3 as follows: Here, n1, n2, and n3 are the numbers of hydrogen atoms in the constituent elements to which the peaks of interest for each site belong. Content of first monomer unit (mol%)= {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 Similarly, the contents of the second monomer unit and the third monomer unit are determined as follows. Content of second monomer unit (mol%)= {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 Content of third monomer unit (mol%)= {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100

[0123] In addition, when a polymerizable monomer that does not contain a hydrogen atom in any component other than the vinyl group is used in the resin, 13 Measure nuclei using C-NMR 13 C, and the measurement was performed in single pulse mode. 1 Calculate in the same manner as above using H-NMR. Based on the molecular weight of the monomer unit, it is possible to convert from mol % to mass %.

[0124] <Method for measuring the peak top temperature of endothermic peaks measured by differential scanning calorimetry (DSC)> The peak top temperature of the endothermic peak measured by differential scanning calorimetry (DSC) of resins, waxes, etc. is measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments). The melting points of indium and zinc are used for temperature correction of the detector of the device, and the heat of fusion of indium is used for heat correction. Specifically, 3 mg of the sample is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference, and the measurement is performed under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 30℃ End of measurement temperature: 180℃ Measurements are performed in the measurement range of 30 to 180°C at a heating rate of 10°C / min. The temperature is raised to 180°C once and held for 10 minutes, then lowered to 30°C, and then raised again. During this second heating process, the peak top temperature of the sample is calculated from the temperature-endothermic curve in the temperature range of 30°C to 80°C.

[0125] <Observation of toner cross section and measurement of matrix domain structure> First, a thin sample was prepared as a reference sample for the amount of the metal. The first resin, which is a crystalline resin, is thoroughly dispersed in a viscoelastic dispersion liquid (LCR Series D800), and then irradiated with short-wavelength light to harden it. The hardened material obtained is cut with an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. In the same manner, a thin sample is also prepared for the second resin, which is an amorphous resin.

[0126] In addition, the first resin and the second resin are mixed in a ratio of 30 / 70 and 70 / 30 by mass, and melt-kneaded to prepare a kneaded product. These are also similarly dispersed in a visible light curable resin, hardened, and then cut out to prepare thin-section samples. Next, the cut-out samples are cross-sectioned using a transmission electron microscope (JEM-2800, manufactured by JEOL Ltd.) (TEM-EDX). The surface is observed and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen. The mapping conditions are as follows: Acceleration voltage: 200 kV Electron beam irradiation size: 1.5 nm Live time limit: 600sec Dead time: 20~30 Mapping resolution: 256×256

[0127] Based on the spectral intensity (average in an area of ​​10 nm square) of each element, calculate (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) and create a calibration curve for the mass ratio of the first resin to the second resin. If the monomer unit of the first resin contains nitrogen atoms, the calibration curve of (nitrogen element intensity / carbon element intensity) will be used for future quantification.

[0128] Next, the toner sample is analyzed. After thoroughly dispersing the toner in a visible light curable resin (Aronix LCR Series D800), it is irradiated with short wavelength light and cured. The resulting cured product is cut out using an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. The cut sample is then observed using a transmission electron microscope (JEOL JEM-2800) (TEM-EDX). Cross-sectional images of the toner particles are obtained, and elemental mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen.

[0129] The toner particle cross section to be observed is selected as follows. First, the cross-sectional area of ​​the toner particle is obtained from the toner particle cross-sectional image, and the diameter (equivalent circle diameter) of a circle having an area equal to the cross-sectional area is obtained. Only toner particle cross-sectional images in which the absolute value of the difference between this equivalent circle diameter and the weight average particle diameter (D4) of the toner particle is within 1.0 μm are observed. For the domains confirmed in the observed image, (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the (average of 10 nm square) spectral intensity of each element, and the ratio of the first resin to the second resin is calculated by comparing with the calibration curve. Domains in which the ratio of the second resin is 80% or more are defined as domains of the present disclosure.

[0130] When the ratio of the toner particle cross section forming a matrix domain structure among the toner particle cross sections is 80% by number or more, the toner particle cross section of the toner to be measured is determined to have a matrix domain structure. The matrix domain structure is a state in which domains, which are discontinuous phases, are dispersed in a matrix, which is a continuous phase. Here, the continuous phase means that, in the toner particle cross section, when 90% or more of the area of ​​the first resin or the area occupied by the second resin exists as one continuous region, the first resin or the second resin is determined to be a continuous phase.

[0131] After identifying the domains confirmed by the observed image, the particle size of the domains present on the cross section of the toner particle is obtained by binarization processing. The particle size is the circle-equivalent diameter of the domain. This is measured at 10 points per toner particle, and the arithmetic average of the domain particle sizes of the 10 toner particles is taken as the number-average circle-equivalent diameter of the domain (μm).

[0132] Meanwhile, the area of ​​the domains is calculated by adding up the areas of all the domains present in one toner particle cross-sectional image to obtain the total area, which is designated as S1. The total area of ​​the domains of 100 toner particles (i.e., S1 + S2... + S100) is calculated, and the arithmetic average value of the 100 particles is designated as the "domain area."

[0133] The cross-sectional area of ​​the toner particles is calculated by calculating the total cross-sectional area of ​​the toner particles (100 toner particles) obtained from the toner cross-sectional images used to calculate the area of ​​the domain, and then calculating the arithmetic average The value is taken as the "total cross-sectional area of ​​the toner particle." Additionally, the "total cross-sectional area of ​​the toner particle" - [domain area] is taken as the [matrix area]. The area ratio of the matrix to the total area of ​​the matrix and domain combined is taken as [matrix area] / ([domain area]+[matrix area])x100. The image processing software "ImageJ" is used for the binarization process and calculation of the number-average diameter.

[0134] <Measurement of Hydrocarbon Group Index (Ge) / Hydrocarbon Group Index (DIA)> First, the toner is washed with hexane to remove low molecular weight materials such as wax. (1) Add 30 mL of hexane to a 100 mL flat-bottom glass beaker. (2) A specified amount of water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W. (3) Set the beaker (1) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (4) While the beaker in (3) is being irradiated with ultrasonic waves, 10 mg of toner is added little by little and dispersed. Then, ultrasonic dispersion treatment is continued for another 5 minutes. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (5) The dispersion obtained in (4) is filtered using a vacuum filter and dried in a dryer for 3 hours or more to obtain a hexane-washed toner.

[0135] FT-IR spectra were obtained using the Universal ATR Measurement Accessory (Universal The measurements were performed using a Fourier transform infrared spectrometer (Spectrum One: PerkinElmer) equipped with an ATR Sampling Accessory. The specific measurement procedure and the method for calculating the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) are as follows. The angle of incidence of infrared light (λ=5μm) is set to 45°. As the ATR crystals, a Ge ATR crystal (refractive index: 4.0) and a diamond ATR crystal (refractive index: 2.4) are used. Other conditions are as follows. When Ge is used as the ATR crystal, the measurement site is approximately 200nm from the sample surface, and when diamond is used, the measurement site is approximately 700nm from the sample surface. Range Start: 4000cm -1 End: 600cm -1 (ATR crystal of Ge) 400cm -1 (ATR crystal of diamond) Duration Scan number: 16 Resolution:4.00cm -1 Advanced: With CO2 / H2O correction

[0136] [Calculation method of hydrocarbon group index (Ge)] (1) A Ge ATR crystal is attached to the apparatus. (2) Set the Scan type to Background and Units to EGY. Measure the background. (3) Set Scan type to Sample and Units to A. (4) 0.01 g of toner is precisely weighed out onto the ATR crystal. (5) Pressurize the sample with the pressure arm (Force Gauge is 90). (6) Measure the sample. (7) The obtained FT-IR spectrum was corrected by Automatic Correction. Perform baseline correction. (8) 2,800 cm -1 ~2900cm -1 Calculate the maximum absorption peak intensity in the range (this is called A1(Ge)). (9) 2,800 cm -1 and 2900cm -1 Calculate the average absorption intensity (this is called A2(Ge)). (10) A1(Ge)-A2(Ge)=A(Ge). The A(Ge) is defined as the 2800 cm -1 ~2900cm -1 The maximum absorption peak intensity in the range is defined as the maximum absorption peak intensity in the range. (11) 1,500 cm -1 ~1800cm -1 The maximum value of the absorption peak intensity in the range is calculated (this is designated as B1(Ge)). (12) 1,500 cm -1 and 1800cm -1 Calculate the average absorption intensity (this is called B2(Ge)). (13) B1(Ge)-B2(Ge)=B(Ge). The B(Ge) is the 1500 cm corresponding to the stretching vibration of C=O. -1 and 1800cm -1 It is defined as the maximum absorption peak intensity in the following range. (14)A(Ge) / B(Ge) = hydrocarbon group index (Ge).

[0137] [Calculation method of Hydrocarbon Group Index (DIA)] (1) A diamond ATR crystal is attached to the instrument. (2) Set the Scan type to Background and Units to EGY. Measure the background. (3) Set Scan type to Sample and Units to A. (4) 0.01 g of toner is precisely weighed out onto the ATR crystal. (5) Pressurize the sample with the pressure arm (Force Gauge is 90). (6) Measure the sample. (7) The obtained FT-IR spectrum was corrected by Automatic Correction. Perform baseline correction. (8) 2,800 cm -1 ~2900cm -1 Calculate the maximum absorption peak intensity in the range (this is called A1(DIA)). (9) 2,800 cm -1 and 2900cm -1 Calculate the average absorption intensity (this is called A2(DIA)). (10) A1(DIA)-A2(DIA)=A(DIA). The A(DIA) is the 2800 cm corresponding to the CH stretching vibration. -1 ~2900cm -1 The maximum absorption peak intensity in the range is defined as the maximum absorption peak intensity in the range. (11) 1,500 cm -1 ~1800cm -1 The maximum absorption peak intensity in the range is calculated (this is designated as B1(DIA)). (12) 1,500 cm -1 and 1800cm -1 Calculate the average absorption intensity (this is called B2(DIA)). (13) B1(DIA)-B2(DIA)=B(DIA). The B(DIA) is the 1500 cm corresponding to the stretching vibration of C=O. -1 and 1800cm -1It is defined as the maximum absorption peak intensity in the following range. (14) A(DIA) / B(DIA) = Hydrocarbon group index (DIA).

[0138] [Calculation method for measuring Hydrocarbon Group Index (Ge) / Hydrocarbon Group Index (DIA)] The hydrocarbon group index (Ge) and the hydrocarbon group index (DIA) obtained as above are used to calculate the hydrocarbon group index (Ge) / hydrocarbon group index (DIA).

[0139] <Method of measuring charge decay> The charge decay rate coefficient of the toner particles was measured using an electrostatic diffusion rate measuring device NS-D100 (manufactured by Nano Seeds Co., Ltd.). First, about 100 mg of toner particles was filled into a sample pan, and the surface was scraped off to make it smooth. The sample pan was irradiated with X-rays using an X-ray static eliminator for 30 seconds, and the toner particles were removed. - The charge on the particles is removed. The charge-removed sample pan is placed on the measurement plate. A metal plate is placed on the plate at the same time as a reference to zero-correct the surface potential meter. The measurement plate with the sample placed on it is left in an environment of 30°C and 80% RH for at least one hour before measurement. The measurement conditions are set as follows: Charge time: 0.1 seconds Measurement time: 1800 seconds Measurement interval: 1 second Discharge polarity:- Electrodes: Yes

[0140] The initial potential was set to -600 V, and the change in surface potential was measured immediately after charging. The charge decay rate coefficient α was calculated by fitting the obtained results to the following equation. V t = V0exp(-αt 1 / 2 ) V t : surface potential at time t (V) V0: Initial surface potential (V) t: Time from application of charge (seconds) α: Charge decay rate coefficient

[0141] <Method of measuring weight-average particle size (D4) of toner (particles)> The weight-average particle diameter (D4) of the toner (particles) is measured with a precision particle size distribution measuring device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data, with an effective measurement channel count of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is one in which special grade sodium chloride is dissolved in ion-exchanged water to a concentration of approximately 1 mass%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing the measurement and analysis, the dedicated software is set up as follows.

[0142] In the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to Particle Size Conversion Setting Screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bin, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.

[0143] (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of Conaminon N is added to this water tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).

[0144] <Method for measuring the 50% particle size (D50) based on volume distribution of resin particles, wax particles, and colorant particles> The 50% particle size (D50) based on the volume distribution of each particle is measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso). Specifically, the measurement is performed according to the following procedure. In order to prevent the measurement sample from agglomerating, a dispersion liquid in which the measurement sample is dispersed is poured into an aqueous solution containing Family Fresh (manufactured by Kao Corporation) and stirred. After stirring, the measurement sample is poured into the above-mentioned device and measured twice to obtain the average value. The measurement conditions are as follows: the measurement time is 30 seconds, the refractive index of the sample particles is 1.49, the dispersion medium is water, and the refractive index of the dispersion medium is 1.33. The volume particle size distribution of the measurement sample is measured, and the particle size at which the cumulative volume from the small particle diameter side in the cumulative volume distribution is 50% from the measurement results is taken as the 50% particle size (D50) based on the volume distribution of each particle.

[0145] <Method of measuring resin softening point (Tm)> The softening point of the resin is measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston, while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature at this time can be obtained. The "melting temperature in the 1 / 2 method" described in the manual that comes with the "Flow characteristic evaluation device Flow Tester CFT-500D" is taken as the softening point. The melting temperature in the 1 / 2 method is calculated as follows.

[0146] First, find 1 / 2 of the difference between the amount of piston descent at the time when the outflow ends (end of outflow, Smax) and the amount of piston descent at the time when the outflow starts (minimum point, Smin) (this is X. X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method. The measurement sample is a cylindrical shape with a diameter of about 8 mm, compressed and molded at about 10 MPa for about 60 seconds using a tablet molding compressor (for example, NT-100H, manufactured by NPA Systems Co., Ltd.) in an environment of 25°C. Specific operations in the measurement are performed according to the manual attached to the device. The measurement conditions for CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf / cm 2 (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm EXAMPLES

[0147] The basic configuration and features of the present invention have been described above, and the present invention will be specifically described below based on examples. However, the present invention is not limited to these. Note that parts and % are based on mass unless otherwise specified.

[0148] <Production Example of Crystalline Resin 1> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, acrylonitrile, and styrene in the ratios shown below.) (Behenyl acrylate (first polymerizable monomer): 55.0 parts) (Acrylonitrile (second polymerizable monomer): 18.0 parts) (Styrene (third polymerizable monomer): 27.0 parts) Polymerization initiator: t-butyl peroxypivalate (NOF Corp.: Perbutyl PV): 0.5 parts

[0149] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. The solution was then cooled to 25°C, and the solution was poured into 1000.0 parts of methanol while stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and vacuum dried at 40°C for 24 hours to obtain crystalline resin 1. The peak top temperature of the temperature-endothermic curve of crystalline resin 1 was 62°C. When the above crystalline resin 1 was analyzed by NMR, it was found to contain 55.0% by mass of monomer units derived from behenyl acrylate, 18.0% by mass of monomer units derived from acrylonitrile, and 27.0% by mass of monomer units derived from styrene.

[0150] <Production Examples of Crystalline Resin 2 to Crystalline Resin 12> Crystalline resins 2 to 12 were obtained by carrying out the reaction in the same manner as in the production example of crystalline resin 1, except that the polymerizable monomers and the parts were changed as shown in Table 1. The obtained crystalline resins were analyzed by NMR, and it was confirmed that, like crystalline resin 1, each monomer unit was contained in the same mass ratio as in the formulation. [Table 1] The unit of SP value is (J / cm 3 ) 0.5 It is.

[0151] The abbreviations in Table 1 are as follows: BEA: Behenyl acrylate SA: Stearyl acrylate MYA: Myricyl acrylate OA: Octacosa acrylate AN: Acrylonitrile AA: Acrylic acid St: styrene

[0152] <Production Example of Crystalline Resin 13> 1,12-dodecanediol: 46.5 parts Dodecanedioic acid: 53.3 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the flask with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours while stirring at a temperature of 140°C. Next, the pressure in the reaction vessel was reduced to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 200°C. After that, the pressure in the reaction vessel was reduced to 5 kPa or less, and the reaction was carried out at 200°C for 3 hours, to obtain crystalline resin 13.

[0153] <Production Examples of Crystalline Resins 14 and 15> Crystalline resins 14 and 15 were obtained by carrying out the same production procedure as in the production example of crystalline resin 13, except that the alcohol component and the carboxylic acid component were changed to the monomers shown in Table 2. [Table 2] The unit of SP value is (J / cm 3 ) 0.5 It is.

[0154] The abbreviations in Table 2 are as follows: DDO: Dodecanediol DDA: Dodecanedioic acid HO: Hexanediol EG: Ethylene glycol AA: Adipic acid

[0155] <Production Example of Amorphous Resin 1> 50.0 parts of xylene was charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 185°C while stirring and sealing. A mixed solution of 75.0 parts of styrene, 25.0 parts of n-butyl acrylate, and 1.0 part of di-tert-butyl peroxide and 20.0 parts of xylene was continuously added dropwise to the autoclave for 3 hours while controlling the temperature inside the autoclave at 185°C, and polymerization was allowed to proceed. The same temperature was maintained for another 1 hour to complete the polymerization, and the solvent was removed to obtain amorphous resin 1. The SP value of amorphous resin 1 was 20.1 (J / cm 3 ) 0.5 The softening point (Tm) was 100°C.

[0156] <Production Example of Amorphous Resin 2> The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 73.4 parts (0.19 moles) Terephthalic acid: 11.6 parts (0.07 moles) Adipic acid: 6.8 parts (0.05 moles) Titanium tetrabutoxide: 2.0 parts Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the mixture was stirred at a temperature of 200°C and reacted for 2 hours while distilling off the water produced. The pressure in the reaction vessel was then lowered to 8.3 kPa and maintained for 1 hour, after which it was cooled to 180°C and returned to atmospheric pressure (first reaction step). Trimellitic anhydride: 8.2 parts (0.04 moles) tert-Butylcatechol (polymerization inhibitor): 0.1 parts The above materials were then added, the pressure in the reaction vessel was lowered to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 150°C. The reaction was then stopped by lowering the temperature (second reaction step), and a second resin, amorphous resin 2, was obtained. The SP value of amorphous resin 2 was 23.3 (J / cm 3 ) 0.5 The softening point (Tm) was 105°C.

[0157] <Toner 1 Manufacturing Example> ·Crystalline resin 1: 50.0 parts Amorphous resin 1: 50.0 parts Wax 1: 5.0 parts (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Colorant 1: 9.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for a rotation time of 5 minutes, the mixture was kneaded at a discharge temperature of 120°C in a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation) set at a temperature of 110°C. The kneaded mixture was cooled and coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product was finely pulverized using a mechanical pulverizer (T-250, manufactured by Freund Turbo Corporation). It was further classified using a Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The operating conditions were a classification rotor speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided.

[0158] The obtained toner particles were subjected to a heat treatment by the surface treatment device shown in FIG. 1 to obtain heat-treated toner particles. The operating conditions were a feed rate of 3 kg / hr, a hot air temperature of 130° C., and a hot air flow rate of 6 m 3 / min., cold air temperature = -5℃, cold air flow rate = 4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min.

[0159] The obtained heat-treated toner particles 1 (100 parts) were surface-treated with 4% by mass of hexamethyldisilazane to obtain a toner having a BET specific surface area of ​​25 m 2 / g hydrophobic silica fine particles, 0.5 parts, BET specific surface area 100 m 2 0.5 parts of hydrophobic silica particles / g were added, and the mixture was mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 30 s-1 The mixture was mixed for a rotation time of 10 minutes to obtain toner 1. The weight average particle size (D4) of toner 1 was about 6.5 μm.

[0160] <Toner Production Example 2> Toner 2 was obtained by carrying out the same production procedure as in Toner Production Example 1, except that the materials were changed to those shown in Table 3.

[0161] <Toner Production Examples 3 to 5> Toners 3 to 5 were obtained by carrying out the same production process as in Toner Production Example 1, except that the hot air temperature during the thermal sphering treatment was changed as shown in Table 3.

[0162] <Production example of crystalline resin 1 fine particle dispersion> Toluene (Wako Pure Chemical Industries, Ltd.) 300 parts ·Crystalline resin 1 100 parts The above materials were weighed, mixed, and dissolved at 100°C. Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion-exchanged water and dissolved by heating at 100°C. Next, the toluene solution and the aqueous solution were mixed and stirred at 7000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, the mixture was emulsified at a pressure of 200 MPa using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo). After that, the toluene was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion liquid (crystalline resin fine particle 1 dispersion liquid) with a concentration of 20% by mass of crystalline resin 1 fine particles. The 50% particle size (D50) based on the volume distribution of crystalline resin 1 was measured using a dynamic light scattering particle size distribution meter Nanotrack UPA-EX150 (manufactured by Nikkiso), and was 0.40 μm.

[0163] <Production Example of Crystalline Resin 2-15 Fine Particle Dispersion> Crystalline resin 2 to 15 microparticle dispersions were obtained by carrying out the same production procedure as in the production example of crystalline resin 1 microparticle dispersion, except that the crystalline materials used were changed.

[0164] <Production example of amorphous resin 1 fine particle dispersion> Tetrahydrofuran (Wako Pure Chemical Industries, Ltd.) 300 parts 100 parts of amorphous resin 1 Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 0.5 parts The above materials were weighed, mixed, and dissolved. Then, 20.0 parts of 1 mol / L ammonia water was added, and the mixture was stirred at 4000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, 700 parts of ion-exchanged water was added at a rate of 8 g / min to precipitate amorphous resin 1 fine particles. Then, tetrahydrofuran was removed using an evaporator. The particles were removed, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (amorphous resin 1 particle dispersion) with a concentration of 20% by mass of amorphous resin 1 fine particles. The volume distribution-based 50% particle size (D50) of the amorphous resin 1 fine particles was 0.14 μm.

[0165] <Production example of amorphous resin 2 fine particle dispersion> Amorphous resin 2 fine particle dispersion was obtained in the same manner as in the production example of amorphous resin 1 fine particle dispersion, except that the amorphous material used was changed.

[0166] <Production Example of Wax Particle Dispersion> Wax 1 100.0 parts (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5 parts 395 parts of ion-exchanged water The above materials were weighed and placed in a mixing vessel equipped with an agitator, then heated to 90°C and circulated through a Clearmix W Motion (manufactured by M Technique) for 60 minutes to perform dispersion processing. The dispersion processing conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min

[0167] After the dispersion process, the mixture was cooled to 40°C under the following cooling conditions: rotor rotation speed 1000 r / min, screen rotation speed 0 r / min, and cooling rate 10°C / min, to obtain an aqueous dispersion of wax microparticles with a concentration of 20% by mass (wax microparticle dispersion). The 50% particle size (D50) based on volume distribution of the wax microparticles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.

[0168] <Production Example of Colorant Microparticle Dispersion> Colorant 1 50.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 7.5 parts 442.5 parts ion-exchanged water The above materials were weighed, mixed, dissolved, and dispersed for about 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain a water-based dispersion of colorant particles with a concentration of 10% by mass (colorant particle dispersion liquid). The 50% particle size (D50) based on the volume distribution of the colorant particles was measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.

[0169] Using each of the dispersions prepared by the above methods, toner particles were prepared by the following method. <Production Example of Toner 6> ·Crystalline resin 1 fine particle dispersion 50.0 parts ·Amorphous resin 1 fine particle dispersion 50.0 parts Wax microparticle dispersion 5.0 parts Colorant fine particle dispersion 9.0 parts 20.0 parts ion-exchanged water Crystalline resin for post-treatment 1 fine particle dispersion 3.0 parts

[0170] All the materials except for the post-treatment crystalline resin 1 fine particle dispersion were placed in a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (IKA) was used. The mixture was dispersed at 5000 r / min for 10 minutes. After adding 1.0% nitric acid aqueous solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The formed aggregated particles were appropriately confirmed using a Coulter Multisizer III, and the mixture was held until the weight average particle size (D4) reached about 6.4 μm. After that, the post-treatment crystalline resin 1 fine particle dispersion was added, and the mixture was held for another 30 minutes, and then the pH was adjusted to 9.0 using a 5% sodium hydroxide aqueous solution.

[0171] Then, while continuing stirring at 500 r / min, the mixture was heated to 75°C. The mixture was then held at 75°C for 1 hour to fuse the aggregated particles. The mixture was then cooled to 50°C and held for 3 hours to promote crystallization of the resin. The mixture was then cooled to 25°C, filtered and separated into solid and liquid, thoroughly washed with ion-exchanged water, and dried to obtain toner particles 6. The weight average particle size (D4) of toner particles 6 was about 6.5 μm. Toner particles 6 thus obtained were externally added with hydrophobic silica fine particles in the same manner as in the manufacturing example of toner 1 to obtain toner 6.

[0172] <Toner Production Examples 7 to 36> Toners 7 to 36 were obtained by carrying out the same production procedure as in Toner Production Example 6, except that the materials and the rotation speed and temperature in the fusing step were changed as shown in Table 3.

[0173] <Toner 37 Manufacturing Example> ·Crystalline resin 12 fine particle dispersion liquid 40.0 parts ·Amorphous resin 1 fine particle dispersion liquid 60.0 parts Wax microparticle dispersion 5.0 parts Colorant fine particle dispersion 9.0 parts 20.0 parts ion-exchanged water 5.0 parts of post-treatment amorphous resin 1 fine particle dispersion All the materials except for the post-treatment amorphous resin 1 fine particle dispersion were put into a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% nitric acid aqueous solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The formed aggregated particles were appropriately confirmed using a Coulter Multisizer III, and the mixture was held until the weight average particle size (D4) reached about 6.3 μm. After that, the post-treatment amorphous resin 1 fine particle dispersion was added, and the mixture was held for another 30 minutes, and then the pH was adjusted to 9.0 using a 5% sodium hydroxide aqueous solution.

[0174] Thereafter, the mixture was heated to 70°C while continuing to stir at 450 r / min. The mixture was then held at 70°C for 1 hour to fuse the aggregated particles. The mixture was then cooled to 50°C and held for 3 hours to promote crystallization of the resin. The mixture was then cooled to 25°C, filtered and separated into solid and liquid, thoroughly washed with ion-exchanged water, and dried to obtain toner particles 37. Toner particles 37 thus obtained were externally added with hydrophobic silica fine particles in the same manner as in the manufacturing example of toner 1 to obtain toner 37.

[0175] The physical properties of the obtained toners 1 to 37 are summarized in Table 4. [Table 3] [Table 4]

[0176] In the table, "area ratio occupied by matrix" indicates the area ratio (area %) occupied by the matrix to the total area including the matrix and domains, and "number-average diameter of domains" indicates the number-average diameter of the equivalent circle diameter of the domains.

[0177] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.

[0178] Phenol: 10% by weight Formaldehyde solution: 6% by mass (40% by mass of formaldehyde, 10% by mass of methanol, 50% by mass of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and held while stirring and mixing, and polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle size (D50) based on volume of the magnetic carrier 1 was 34.2 μm.

[0179] <Production Examples of Two-Component Developers 1-37> Each of toners 1 to 37 and magnetic carrier 1 (50% particle size by volume: 34.2 μm) were mixed in a V-type mixer (V-10 type: Tokuju Seisakusho Co., Ltd.) for 0.5 s to obtain a toner concentration of 9% by mass. -1 The mixture was mixed for 5 minutes to obtain two-component developers 1 to 37.

[0180] <Toner Evaluation> The image forming apparatus used was a modified Canon full-color copier imagePRESS C800, and two-component developer 1 was placed in the cyan station developer. The modifications to the apparatus included the fixing temperature, process speed, and DC voltage V DC , the charging voltage of the electrostatic latent image carrier V D The laser power and the laser power can be freely set. The image output evaluation is performed by outputting a FFh image (solid image) with the desired image ratio, and adjusting the V so that the amount of toner on the FFh image on the paper is as desired. DC , V D The evaluation described below was performed by adjusting the laser power and the color level. FFh is a value obtained by expressing 256 gradations in hexadecimal, with 00h being the first gradation (white background) of the 256 gradations and FFh being the 256th gradation (solid background) of the 256 gradations. Evaluation was performed based on the following evaluation method, and the results are shown in Table 5.

[0181] [Low temperature fixability] Paper: Mondi color copy paper (300g / m 2 ) (Sold by mondi) Toner load on paper: 1.20mg / cm 2 (FFh image) (The DC voltage of the developer carrier V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Evaluation image: A 2cm x 5cm image placed in the center of the A4 paper. Test environment: Low temperature and low humidity environment: Temperature 15℃ / Humidity 10%RH (hereinafter referred to as "L / L") Fixing temperature: 170℃ Process speed: 348mm / sec

[0182] The above evaluation image was output, and the low-temperature fixability was evaluated. The value of the image density reduction rate was used as an evaluation index for the low-temperature fixability. The image density reduction rate was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation) by first measuring the image density at the center. Next, the part where the image density was measured was subjected to pressure of 4.9 kPa (50 g / cm 2The fixed image was rubbed (five times back and forth) with Silbon paper under a load of 1000 g / m2, and the image density was measured again. The rate of decrease in image density before and after rubbing was calculated using the following formula. The resulting rate of decrease in image density was evaluated according to the following evaluation criteria. Evaluations of A to E were judged to be good. Image density reduction rate = (Image density before rubbing - Image density after rubbing) / (Image density before rubbing) x 100 (Evaluation Criteria) A: Image density reduction rate is less than 0.5% B: Image density reduction rate: 0.5% or more and less than 1.0% C: Image density reduction rate: 1.0% or more and less than 2.0% D: Image density reduction rate: 2.0% or more and less than 3.0% E: Image density reduction rate: 3.0% or more and less than 4.0% F: Image density reduction rate: 4.0% or more and less than 5.0% G: Image density reduction rate 5.0% or more

[0183] [Emboss transferability] Paper: Lezac 66 (302 g / m 2 ) (Embossed paper, sold by Tokai Tokushu Paper Co., Ltd.) Toner load on paper: 0.90mg / cm 2 (FFh image) (Mondi color copy paper (250g / m 2 ) (sold by Mondi) to check the amount of toner on the paper in advance, and the DC voltage V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Evaluation image: Image placed on the entire A4 surface of Lezac 66 Fixing test environment: Normal temperature and humidity environment (temperature 23°C / humidity 50% RH (hereinafter N / N)) Fixing temperature: 180℃ Process speed: 173mm / sec

[0184] The above evaluation image was output, and the emboss transferability was evaluated. The standard deviation of the brightness was used as the evaluation index for the emboss transferability. Using a scanner manufactured by ) with a reading resolution of 1200 dpi and image correction processing OFF, the image was read and trimmed to a range of 2,550 x 2,550 pixels (approximately 10.8 x 10.8 cm). Next, a luminance value histogram (vertical axis: frequency (number of pixels), horizontal axis: luminance, luminance value is expressed in the range of 0 to 255) of the image data described above was obtained. In addition, the luminance standard deviation of the image data was calculated based on the obtained luminance value histogram. If the evaluation was A to L, it was judged to be good. The image processing software "ImageJ" was used to calculate the luminance standard deviation. (Evaluation criteria: luminance standard deviation) A: Less than 2.0 B: 2.0 or more and less than 5.0 C: 5.0 or more and less than 8.0 D: 8.0 or more and less than 11.0 E: 11.0 or more and less than 14.0 F: 14.0 or more and less than 17.0 G: 17.0 or more and less than 20.0 H: 20.0 or more and less than 23.0 I: 23.0 or more and less than 26.0 J: 26.0 or more and less than 29.0 K: 29.0 or more and less than 32.0 L: 32.0 or more and less than 35.0 M: 35.0 or more and less than 38.0 N: 38.0 or more and less than 41.0 O:41.0 or more

[0185] Two-component developers 2 to 37 were also evaluated in the same manner as two-component developer 1. The results are shown in Table 5. [Table 5]

Claims

1. A toner having toner particles containing a binder resin, The binder resin contains a first resin and a second resin, the first resin is a crystalline resin; the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, a matrix domain structure is present, which is composed of a matrix in which 90% or more of the area of ​​the first resin exists as one continuous region, and a domain in which the ratio of the second resin in the ratio of the first resin to the second resin calculated based on the spectrum intensity measured by TEM-EDX is 80% by mass or more; an area ratio of the matrix including the first resin to a total area of ​​the matrix and the domain is 35 area % or more and 70 area % or less; The toner is characterized in that the ratio of the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) after the toner is washed with hexane is 1.10 or more. [The hydrocarbon group index (Ge) is the 2800 cm corresponding to the stretching vibration of C—H in the FT-IR spectrum obtained by the ATR method using Ge as the ATR crystal and measuring at an infrared light incidence angle of 45°. -1 ~2900cm -1 The maximum absorption peak intensity in the range of 1500 cm corresponding to the stretching vibration of C=O is defined as A(Ge). -1 ~1800cm -1 The hydrocarbon group index (DIA) is the value of A(Ge) / B(Ge) when the maximum absorption peak intensity in the range is B(Ge). The hydrocarbon group index (DIA) is the value of the maximum absorption peak intensity in the range of A(Ge) / B(Ge) when the maximum absorption peak intensity in the range of B(Ge) ... -1 ~2900cm -1 The maximum absorption peak intensity in the range of 1500 cm corresponding to the stretching vibration of C=O is defined as A(DIA). -1 ~1800cm -1 is the value of A(DIA) / B(DIA) when the maximum absorption peak intensity in the range is B(DIA).

2. 2. The toner according to claim 1, wherein, upon cross-sectional observation of the toner particle, the number average equivalent circle diameter of the domains is 20 nm or more and 500 nm or less.

3. 3. The toner according to claim 1, wherein the toner particles have a charge decay rate coefficient of 10 to 70 as measured in an environment of 30° C. and 80% RH.

4. 4. The toner according to claim 1, wherein the first resin has a first monomer unit represented by the following formula (1): [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.

5. 5. The toner according to claim 4, wherein the content of the first monomer unit in the first resin is 30.0% by mass or more and 80.0% by mass or less.

6. 6. The toner according to claim 1, wherein the second resin is a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof.

7. 7. The toner according to claim 1, wherein the second resin is a styrene-acrylic resin.

8. 8. The toner according to claim 1, wherein the hydrocarbon group index (Ge) / hydrocarbon group index (DIA) is 1.20 or more and 1.60 or less.

9. A method for producing the toner according to any one of claims 1 to 8, comprising the steps of: The method for producing a toner includes a step of performing a surface treatment on the toner particles with hot air to obtain heat-treated toner particles.

Citation Information

Patent Citations

  • Toner, developer, and image forming device

    JP2014059489A

  • Toner

    JP2014130243A

  • Toner

    JP2014142632A

  • Toner and two-component developer

    JP2019219641A

  • Method for producing toner

    JP2022093277A